Using Social Media to Engage Communities with Research: Accessibility - Kathryn A. Stofer; Kirsten Hecht; Lisa Lundgren (EDIS)
This new 6-page document, part of a series on using social media to engage communities with research, focuses on making your social media inclusive by integrating accessibility up front for individuals with disabilities of various types. Any Extension personnel, researchers, and other public engagement and communications personnel can benefit from these strategies. Written by Kathryn A. Stofer, Kirsten Hecht, and Lisa Lundgren, and published by the UF/IFAS Department of Agricultural Education and Communication. https://edis.ifas.ufl.edu/wc427